Skin barrier function and changes of serum inflammatory factor level in hyperpigmentation disorders treated with Nd:YAG laser: Inflammatory factor level in hyperpigmentation disorders - Xu, Chen (Cellular and Molecular Biology, 2023)
It was to compare the differences in efficacy and safety for the treatment of hyperpigmentation disorders by Q-switched alexandrite (Q-SA) laser and Neodymium-doped Yttrium Aluminium Garnet (Nd:YAG) laser. The clinical data of 86 patients with hyperpigmentation disorders were collected and grouped: in the Q-SA laser and Nd:YAG laser groups according to the treatment methods, with 43 cases in each group. The clinical efficacy, skin barrier function (transdermal water loss (TEWL), stratum corneum water content, pH value, proteoglycan content), degree of pigmentation, serum inflammatory factors (high-sensitivity C-reactive protein (hs-CRP), tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6)), and adverse reaction rate were compared after treatment. Compared with the Q-SA laser group, Nd:YAG laser group had decreased scab formation, healing, and scab shedding time, TEWL, pH value, and proteoglycan content, the increased water content of stratum corneum, decreased pigmentation score and area, and decreased serum levels of hs-CRP, TNF-α, and IL-6 (P<0.05). The total effective rates were 76.74% and 95.35%, and the adverse reaction rates were 30.23% and 6.98%, respectively in the Q-SA laser and Nd:YAG laser groups. Compared with the Q-SA laser group, Nd:YAG laser group had a higher total effective rate and lower incidence rate of adverse reactions (P<0.05). Nd:YAG laser plus rhEGF gel in the treatment of hyperpigmentation disorders can effectively protect the skin barrier function, reduce skin pigmentation, reduce the inflammatory response, and improve the therapeutic effect, with high safety.